2021
DOI: 10.3390/ma14247661
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Al Concentration on Microstructure and Properties of AlNbTiZr Medium-Entropy Alloy Coatings

Abstract: The AlNbTiZr medium-entropy alloy (MEA) coatings with different Al contents were prepared on N36 zirconium alloy substrates by RF magnetron co-sputtering. The morphology, microstructure, mechanical properties, surface wettability and corrosion resistance of the AlNbTiZr MEA coatings were studied to evaluate the surface protection behavior of zirconium alloy cladding under operation conditions of a pressurized water reactor. The results showed that all the coatings were composite structures with amorphous and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 45 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…It was shown that the addition of Al initially decreased the hardness and the elasticity, but both increased after increasing the Al content. Additionally, the corrosion resistance was significantly improved [58]. Furthermore, the alloy might have better irradiation resistance [59].…”
Section: Coatings With Meamentioning
confidence: 96%
“…It was shown that the addition of Al initially decreased the hardness and the elasticity, but both increased after increasing the Al content. Additionally, the corrosion resistance was significantly improved [58]. Furthermore, the alloy might have better irradiation resistance [59].…”
Section: Coatings With Meamentioning
confidence: 96%